2010
DOI: 10.1186/1471-244x-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Multiple barriers against successful care provision for depressed patients in general internal medicine in a Japanese rural hospital: a cross-sectional study

Abstract: BackgroundA general internist has an important role in primary care, especially for the elderly in rural areas of Japan. Although effective intervention models for depressed patients in general practice and primary care settings have been developed in the US and UK medical systems, there is little information regarding even the recognition rate and prescription rate of psychotropic medication by general internists in Japan. The present study surveyed these data cross-sectionally in a general internal medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…The finding is compatible with a notion that nonpsychiatrists are reluctant to manage patients with depression (Ohtsuki et al, 2010), and they tend to think that treatment of depression is reserved to only psychiatrists (Ohtsuki et al, 2012). Furthermore, they indicated to judge the efficacy of antidepressants in 8.6 days after prescribing them, which is rather hasty in light of the recommended duration of 2-4 weeks in the guidelines (NICE, 2009).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The finding is compatible with a notion that nonpsychiatrists are reluctant to manage patients with depression (Ohtsuki et al, 2010), and they tend to think that treatment of depression is reserved to only psychiatrists (Ohtsuki et al, 2012). Furthermore, they indicated to judge the efficacy of antidepressants in 8.6 days after prescribing them, which is rather hasty in light of the recommended duration of 2-4 weeks in the guidelines (NICE, 2009).…”
supporting
confidence: 64%
“…In Japan, it has been reported that only 7.4% of patients with depression received optimal treatment in a general hospital (Ohtsuki et al, 2010) despite at least equivalent prevalence of depression in medical inpatients compared to those in other countries (21.5% vs. 5.0-21.0%) (Forkmann et al, 2011;Hosaka et al, 1999;Silverstone et al, 1996). This condition may be, at least to some extent, attributable to lack of confidence, recognition, and motivation towards depressive care among non-psychiatrists (Ohtsuki et al, 2010(Ohtsuki et al, , 2012. Moreover, such non-psychiatrists' negative attitude on depression may result in insufficient utility of consultation-liaison psychiatry; however, the attitude on depression among non-psychiatrists in general hospitals remains unclear.…”
mentioning
confidence: 99%
“…First, the prevalence of depression was high compared with previous reports from Japan (Yamazaki et al 2005;Nakao and Yano 2006;Ohtsuki et al 2010). This might be partly attributable to different methodologies.…”
Section: Discussionmentioning
confidence: 74%
“…Although depression and anxiety are common in primary care settings (Brown and Schulberg 1998;Valenstein et al 2001), these disorders remain undiagnosed and untreated at least half the time (Schulberg and Burns 1988;Zich et al 1990;Ohtsuki et al 2010). In all parts of the world, the vast majority of depressed patients are reported to have visited a primary health care clinic (Patel 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps one explanation for this is that the primary concern for these parents is the health and well-being of their child, which takes priority above their own health needs. However, others have found that primary care physicians are not well-equipped for screening for depression and more effective training is needed to improve detection rates (Ohtsuki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%